2020
DOI: 10.3892/etm.2020.9027
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of vascular intervention combined with intravenous thrombolysis in treatment of acute intracranial arterial occlusion

Abstract: Efficacy and safety of vascular intervention combined with intravenous thrombolysis (IVT) was investigated in the treatment of acute intracranial arterial occlusion (AIAO). Ninety-two patients with AIAO treated in People's Hospital of Tongchuan from January 2014 to February 2016 were enrolled in this retrospective study. Forty-two patients were treated with vascular intervention (control group), while another 50 patients were treated with vascular intervention combined with IVT (study group). They were observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…In the present study, mRS was used to assess the neurological function recovery of the patients and we found that the mRS scores were lower in patients received the IVT+EVT approach, which is consistent with the findings by Huo et al 8 and Zhu et al 12 . In addition, our findings on the incidence of MACE after treatment support the study by Yang et al 21 that there was no significant difference in incidence rate of MACE in patients received EVT alone or IVT+EVT.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In the present study, mRS was used to assess the neurological function recovery of the patients and we found that the mRS scores were lower in patients received the IVT+EVT approach, which is consistent with the findings by Huo et al 8 and Zhu et al 12 . In addition, our findings on the incidence of MACE after treatment support the study by Yang et al 21 that there was no significant difference in incidence rate of MACE in patients received EVT alone or IVT+EVT.…”
Section: Discussionsupporting
confidence: 92%
“… 7 - 9 , 17 - 20 Some studies have found that patients with ACI who received IVT+EVT had better recanalization rates. 8 , 12 , 17 , 20 A shorter time from symptom onset to recanalization was associated with better clinical outcomes and neurological function in patients with ACI. 12 Further evidence shows that EVT following IVT may improve the vascular recanalization rate, subsequently improving survival and recovery in patients with acute ischemic stroke.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations